Solid electrolyte assembly and method for producing same

The solid electrolyte assembly with platinum group elements and oxygen storage metal oxides in the first electrode addresses conductivity and responsiveness issues, enhancing performance in oxide ion conductive solid electrolytes for stable high-current output and sensor applications.

JP7602908B2Active Publication Date: 2024-12-19MITSUI MINING & SMELTING CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2020214301
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-23
Publication Date
2024-12-19
Estimated Expiration
2040-12-23

AI Technical Summary

Technical Problem

Existing technologies for oxide ion conductive solid electrolytes do not adequately address issues of oxide ion conductivity and responsiveness to changes in atmospheric gas concentration, leading to potential voltage drops and instability in high current output states.

Method used

A solid electrolyte assembly comprising a first electrode, a second electrode, and a solid electrolyte with oxide ion conductivity, where the first electrode includes platinum group elements or gold and a metal oxide with oxygen storage ability, formed using a sputtering method, enhancing oxide ion conductivity and responsiveness.

Benefits of technology

The assembly achieves high oxide ion conductivity and improved responsiveness to oxygen gas concentration changes, stabilizing performance and reducing electrical resistance, suitable for applications like oxygen sensors and fuel cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007602908000002
    Figure 0007602908000002
  • Figure 0007602908000003
    Figure 0007602908000003
  • Figure 0007602908000004
    Figure 0007602908000004
Patent Text Reader

Abstract

To provide a solid electrolyte conjugate having high oxide ion conductivity and good responsiveness of an oxide ion current value to a change in oxygen gas concentration.SOLUTION: A solid electrolyte conjugate 1 includes a first electrode 11, a second electrode 12, and a solid electrolyte 13 located between both the electrodes 11 and 12. The solid electrolyte 13 is a ceramic having oxide ion conductivity. The first electrode 11 includes at least one of platinum group elements, gold, and alloys containing these, and a metal oxide having an oxygen occlusion ability. It is preferable that the metal oxide is an oxide of Ce alone, an oxide containing Ce and Zr, or an oxide containing Ce and Zr, which is an oxide in which a part of Ce or Zr is replaced with at least one rare earth element other than Ce.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a solid electrolyte joint and a method for producing the same. [Background technology]

[0002] A known prior art related to solid electrolyte assemblies is described in Patent Document 1. The document describes that a catalyst layer disposed adjacent to a solid electrolyte membrane in a fuel cell contains platinum and a metal oxide having oxygen storage capacity. In the fuel cell described in the document, the oxygen storage and release function of the metal oxide causes oxygen dissolved in an aqueous solvent to be stored in the metal oxide when there is no oxygen shortage during power generation, and causes oxygen to be released from the metal oxide to the aqueous solvent when there is a shortage of oxygen during power generation. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. 2010 / 131536 Brochure Summary of the Invention [Problem to be solved by the invention]

[0004] The technology described in Patent Document 1 relates to providing a polymer electrolyte fuel cell that is unlikely to suffer from a voltage drop even in a high current output state and is capable of supplying stable power. In other words, the technology relates to a fuel cell that uses a proton-conductive solid polymer as an electrolyte. However, the document does not consider the application of the technology described in the document to an oxide-ion conductive solid electrolyte. Therefore, the technology described in the document does not solve the problems associated with devices that use an oxide-ion conductive solid electrolyte, such as improving oxide-ion conductivity and oxide-ion current value responsiveness to changes in atmospheric gas concentration. SUMMARY OF THE PRESENT EMBODIMENTS An object of the present invention is to provide a solid electrolyte assembly which can overcome the above-mentioned drawbacks of the prior art. [Means for solving the problem]

[0005] The present invention provides a solid electrolyte junction including a first electrode, a second electrode, and a solid electrolyte located between the first and second electrodes, the solid electrolyte is a ceramic having oxide ion conductivity, The present invention provides a solid electrolyte joint, wherein the first electrode contains at least one of a platinum group element, gold, and an alloy containing these, and a metal oxide having an oxygen storage capacity.

[0006] The present invention also provides a method for manufacturing a semiconductor device, comprising the steps of: forming an amorphous first electrode, the first electrode including at least one of a platinum group element, gold, and an alloy including these, and a metal oxide having an oxygen storage capacity, by a sputtering method; forming an amorphous solid electrolyte on the first electrode by a sputtering method; and forming a second electrode on the solid electrolyte by a sputtering method. The present invention provides a method for producing a solid electrolyte junction, which comprises performing a step of forming a first electrode, followed by a step of forming a solid electrolyte and a step of forming a second electrode, or performing a step of forming a second electrode, followed by a step of forming a solid electrolyte and a step of forming a first electrode. Effect of the Invention

[0007] According to the present invention, there is provided a solid electrolyte joint having high oxide ion conductivity and good responsiveness of the oxide ion current value to changes in oxygen gas concentration. [Brief description of the drawings]

[0008] [Figure 1] FIG. 1 is a schematic cross-sectional view showing one embodiment of a solid electrolyte joined body of the present invention. [Diagram 2]FIG. 2 is a schematic cross-sectional view showing another embodiment of a solid electrolyte joined body of the present invention. [Diagram 3] FIG. 3 is a cross-sectional view showing a solid electrolyte joined body according to still another embodiment of the present invention. [Figure 4] FIG. 4 is a schematic cross-sectional view showing still another embodiment of a solid electrolyte joined body of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The present invention will be described below based on its preferred embodiments. The solid electrolyte joint of the present invention includes, as its constituent members, a first electrode, a second electrode, and a solid electrolyte located between the two electrodes. The first electrode and the solid electrolyte are generally in direct contact over the entire area of ​​their opposing surfaces, but may be in direct contact with each other partially within the scope of the object of the present invention, or may have some layer interposed between them. Similarly, the second electrode and the solid electrolyte are generally in direct contact over the entire area of ​​their opposing surfaces, but may be in direct contact with each other partially within the scope of the object of the present invention, or may have some layer interposed between them.

[0010] The solid electrolyte layer is made of a ceramic material having oxide ion conductivity. The type of the solid electrolyte is not particularly limited as long as it has oxide ion conductivity, and various conventionally known materials can be used.

[0011] The solid electrolyte with oxide ion conductivity is M 1 , M 2 and O. By using such a compound, it is possible to further increase the oxide ion conductivity of the solid electrolyte. 1 is one or more elements selected from the group consisting of La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Yb, Lu, Be, Mg, Ca, Sr, Y, Ba and Bi. 2is one or more elements selected from the group consisting of Mg, Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Ga, Zr, Ta, Nb, B, Si, Ge, Zn, Sn, W, and Mo. The compound preferably has an apatite-type crystal structure.

[0012] In particular, the solid electrolyte is represented by the formula (1)M 1 9.33+x [T 6.00-y M 2 y ]O 26.0+z In order to further increase the oxide ion conductivity of the solid electrolyte, it is preferable to contain a composite oxide represented by the formula: 1 As described above, is one or more elements selected from the group consisting of La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Yb, Lu, Be, Mg, Ca, Sr, Y, Ba and Bi. T is an element containing Si or Ge or both. M 2 is one or more elements selected from the group consisting of Mg, Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Ga, Zr, Ta, Nb, B, Zn, Sn, W, and Mo. x is a number between -1.33 and 1.50. y is a number between 0.00 and 3.00. z is a number between -5.00 and 5.20. The ratio of M to the number of moles of T 1 The molar ratio of these is equal to or greater than 1.33 and equal to or less than 3.61. The composite oxide preferably has an apatite-type crystal structure.

[0013] In formula (1), M 1The elements listed as above, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Yb, Lu, Be, Mg, Ca, Sr, Y, Ba and Bi, are elements that have in common that they are lanthanoids or group 2 elements that can become positively charged ions and form an apatite-type hexagonal crystal structure. Among these, from the viewpoint of further increasing the oxide ion conductivity, it is preferable to use a combination of one or more elements selected from the group consisting of La, Nd, Ba, Sr, Ca, Y, Bi and Ce, and among these, it is preferable to use a combination of one of La or Nd, or one or more elements selected from the group consisting of La and Nd, Ba, Sr, Ca, Y, Bi and Ce. In addition, T in formula (1) is preferably an element containing Si or Ge or both.

[0014] M in formula (1) 2 Preferred examples of the element include one or more elements selected from the group consisting of Mg, Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Ga, Zr, Ta, Nb, B, Zn, Sn, W, and Mo. Among these, B, Zn, and W are particularly preferred from the viewpoint of increasing the oxide ion conductivity.

[0015] In formula (1), x is preferably a number between -1.33 and 1.50, more preferably between -1.00 and 1.00, and even more preferably between 0.00 and 0.70, and even more preferably between 0.45 and 0.65. In formula (1), y is preferably a number between 0.00 and 3.00, more preferably between 0.40 and less than 1.00, and even more preferably between 0.40 and 0.90, and even more preferably between 0.80 and 0.70, and even more preferably between 0.50 and 0.70, from the viewpoint of filling the T element position in the apatite-type crystal lattice and the viewpoint of increasing the oxide ion conductivity. From the viewpoint of maintaining electrical neutrality in the apatite-type crystal lattice, z in formula (1) is preferably a number of −5.00 or more and 5.20 or less, preferably −3.00 or more and 2.00 or less, more preferably −2.00 or more or 1.50 or less, and most preferably −1.00 or more or 1.00 or less.

[0016] In formula (1), M relative to the number of moles of T 1 The ratio of the number of moles of x, in other words (9.33+x) / (6.00-y), is preferably 1.33 or more and 3.61 or less, more preferably 1.40 or more and 3.00 or less, and even more preferably 1.50 or more and 2.00 or less, from the viewpoint of maintaining the spatial occupancy rate in the apatite-type crystal lattice.

[0017] Among the composite oxides represented by formula (1), M 1 The composite oxide in which the lanthanum is 9.33+x [T 6.00-y M 2 y ]O 26.0+z It is preferable to use a composite oxide represented by the formula: La 9.33+x [T 6.00-y M 2 y ]O 26.0+z Specific examples of composite oxides represented by the formula are La 9.33+x (Si 5.30 B0.70 )O 26.0+z , La 9.33+x (Si 4.70 B 1.30 )O 26.0+z , La 9.33+x (Si 4.70 Ge 1.30 )O 26.0+z , La 9.33+x (Si 4.70 Zinc 1.30 )O 26.0+z , La 9.33+x (Si 4.70 W 1.30 )O 26.0+z , La 9.33+x (Si 4.70 Sn 1.30 )O 26.0+z , La 9.33+x (Ge 4.70 B 1.30 )O 26.0+z Among the composite oxides represented by formula (1), M 1 Particularly preferred is a composite oxide in which T is lanthanum and T is Si, that is, a composite oxide containing lanthanum and silicon. The composite oxide represented by formula (1) can be produced, for example, according to the method described in International Publication WO2016 / 111110.

[0018] The solid electrolyte is preferably at least one selected from the group consisting of not only the above-mentioned composite oxide containing lanthanum and silicon, but also yttrium-stabilized zirconia (hereinafter referred to as "YSZ"), samarium-doped ceria (hereinafter referred to as "SDC"), gadolinium-doped ceria (hereinafter referred to as "GDC"), lanthanum gallate, and yttrium-doped bismuth oxide (hereinafter referred to as "YBO").

[0019] As the YSZ, it is preferable to use one in which the ratio of the number of moles of yttrium to the total number of moles of zirconium (Zr) and yttrium (Y) (Y / (Zr+Y)) is 0.05 or more and 0.15 or less. As the SDC, it is preferable to use one in which the ratio of the number of moles of samarium to the total number of moles of cerium (Ce) and samarium (Sm) (Sm / (Ce+Sm)) is 0.10 or more and 0.25 or less. As the GDC, it is preferable to use one in which the ratio of the number of moles of gadolinium to the total number of moles of cerium (Ce) and gadolinium (Gd) (Gd / (Ce+Gd)) is 0.10 or more and 0.25 or less. As the YBO, it is preferable to use one in which the ratio of the number of moles of yttrium to the total number of moles of bismuth (Bi) and yttrium (Y) (Y / (Bi+Y)) is 0.10 or more and 0.30 or less.

[0020] The solid electrolyte may be one of the above-mentioned materials or a combination of two or more of them. When two or more materials are used, the materials may be laminated or mixed.

[0021] In the solid electrolyte joint of the present invention, when the solid electrolyte has a layered form, the thickness thereof is preferably from 10 to 1000 nm, more preferably from 30 to 500 nm, and even more preferably from 50 to 300 nm, from the viewpoint of increasing the oxide ion conductivity of the solid electrolyte joint and effectively reducing the electrical resistance. The thickness of the solid electrolyte can be measured by cross-sectional observation using a stylus step gauge or an electron microscope.

[0022] The first electrode in the solid electrolyte junction of the present invention functions as an electrode of the above-mentioned solid electrolyte. For this purpose, the first electrode contains an element having oxygen reduction catalytic activity among metal elements, that is, an element including at least one of platinum group elements, gold, and alloys containing these (hereinafter, these elements are collectively referred to as "platinum, etc."). The first electrode is also configured to contain a metal oxide having oxygen storage ability (hereinafter, also referred to as "OSC material").

[0023] The present inventors have found that the oxide ion conductivity of the solid electrolyte joint of the present invention is increased and the electrical resistance is reduced by including platinum or the like and an OSC material in the first electrode. The reduction in electrical resistance of the solid electrolyte joint brings about an advantage such as stabilization of sensor behavior when the solid electrolyte joint is used as, for example, an oxygen sensor. Specifically, when the solid electrolyte joint of the present invention is used as, for example, an oxygen sensor, the responsiveness of the oxide ion current to changes in oxygen gas concentration is improved. From the viewpoint of making this advantage more prominent, it is preferable that platinum or the like and the OSC material form a compound or are mixed in the first electrode.

[0024] The phrase "Platinum etc. and the OSC material form a compound" refers to, for example, a state in which the cations of the platinum etc. and the OSC material diffuse into each other and are partially dissolved in solid solution, or a state in which the platinum etc. and the elements constituting the OSC material form an alloy or a complex oxide. A state in which platinum or the like and the OSC material are mixed together means, for example, that platinum or the like is not dissolved in the OSC material, but is mixed with the OSC material while maintaining their independent properties, such as a cocontinuous structure or a partially dispersed structure.

[0025] From the viewpoint of increasing the oxide ion conductivity of the solid electrolyte junction and reducing the electrical resistance, in the first electrode containing platinum or the like and an OSC material, the platinum or the like and the OSC material are preferably in the form of a so-called cermet. For example, in the first electrode, the platinum or the like and the OSC material preferably have a co-continuous structure. In order to give the first electrode such a co-continuous structure, the first electrode may be formed by, for example, a method described below. Whether the first electrode has a co-continuous structure or not can be confirmed by, for example, cross-sectional observation using a scanning electron microscope (SEM) or a transmission electron microscope (TEM) and energy dispersive X-ray spectroscopy (EDS).

[0026] The ratio of the OSC material in the first electrode is preferably 1% by volume to 50% by volume, more preferably 2% by volume to 40% by volume, and even more preferably 3% by volume to 30% by volume, expressed in terms of a volume calculated from the deposition rate of a single film of platinum or the like and the deposition rate of the OSC material. Setting the ratio of the OSC material in the first electrode within this range is advantageous from the viewpoint of ensuring electronic conductivity in the first electrode and functioning adequately as a solid electrolyte electrode.

[0027] From a similar viewpoint, the proportion of platinum or the like in the first electrode, expressed in terms of volume calculated from the deposition rate of a single film of platinum or the like and the deposition rate of the OSC material, is preferably 50 vol. % or more and 99 vol. % or less, more preferably 60 vol. % or more and 98 vol. % or less, and even more preferably 70 vol. % or more and 97 vol. % or less.

[0028] The ratio of the OSC material and the ratio of platinum, etc. in the first electrode can be measured by the following method. The OSC material and platinum, etc. are separately formed on a substrate, and the thickness of each is measured using a stylus-type step height gauge, so that the ratio of each can be calculated when the OSC material and platinum, etc. are simultaneously formed. Alternatively, EDS measurement is performed using a SEM or TEM, and quantitative analysis is performed by converting the atomic ratio of each element in the film into a volume using the density.

[0029] The first electrode may be porous. This allows the gas to diffuse through the first electrode, which may promote the electrochemical reaction. In this case, the first electrode preferably has an average porosity of 0.1% to 15%, more preferably 0.2% to 10%.

[0030] The average porosity is measured, for example, by the following method. First, a secondary electron image of the surface of the first electrode in which the void and non-void parts are clearly distinguishable is obtained using an SEM under conditions of an acceleration voltage of 5 kV and a magnification of 5000 times. The image contrast of the obtained image is appropriately adjusted so that the void and non-void parts can be distinguished by brightness. A 23 μm×17 μm range of the obtained image is binarized using Image-Pro (registered trademark) (manufactured by Media Cybernetics) into bright parts consisting of non-void parts and dark parts consisting of void parts, and the area ratio is measured to obtain the average porosity.

[0031] In the solid electrolyte joint of the present invention, when the first electrode has a layered form, its thickness is preferably 10 nm to 1000 nm, more preferably 50 nm to 500 nm, and even more preferably 100 nm to 400 nm. By setting the thickness of the first electrode within this range, it is possible to ensure electronic conductivity within the first electrode layer, and the first electrode functions sufficiently as an electrode of the solid electrolyte. The thickness of the first electrode can be measured by cross-sectional observation using a stylus step gauge or an electron microscope.

[0032] The platinum and other components constituting the first electrode are preferably present in the first electrode in the form of a single metal. In this specification, the platinum group element refers to any of the elements Pt, Pd, Rh, Ir, Ru, and Os. The alloy containing a platinum group element or gold refers to an alloy containing at least a platinum group element or gold in part. Examples of alloy constituent elements other than the platinum group elements and gold include transition metal elements such as Ni and Fe. It is preferable to use Pt as the platinum and other metals used in the first electrode in order to enhance the oxygen reduction catalytic activity of the electrode.

[0033] The OSC material, which is a component constituting the first electrode together with platinum and the like, is made of a metal oxide having oxygen storage capacity as described above. As the OSC material, a material capable of absorbing and releasing oxygen according to the oxygen gas concentration in the atmosphere is used. From this viewpoint, it is preferable that the metal constituting the OSC material is a polyvalent metal. As examples of metal oxides constituting the OSC material, cerium oxide, iron oxide, copper oxide, and oxides of rare earth elements other than cerium are preferably used from the viewpoint of thermal stability, etc. Examples of oxides of rare earth elements other than cerium include Sc2O3, Y2O3, La2O3, Pr6O 11 , Nd2O3, Sm2O3, Eu2O3, Gd2O3, Tb4O7, Dy2O3, Ho2O3, Er2O3, Tm2O3, Yb2O3 and Lu2O3.

[0034] In particular, it is preferable that the OSC material is an oxide containing cerium, from the viewpoint of increasing the oxide ion conductivity of the solid electrolyte joint of the present invention and further reducing the electrical resistance. From this viewpoint, when the OSC material is an oxide containing cerium, the oxide is preferably at least one selected from the following (1) to (3): (1) Ce oxide. (2) An oxide containing Ce and Zr. (3) An oxide containing Ce and Zr, in which a portion of Ce or Zr is replaced with at least one rare earth element other than Ce.

[0035] When the oxide containing cerium is (1), the oxide is generally represented as CeO2.

[0036] When the oxide containing cerium is (2), the oxide is generally a solid solution of CeO2 and ZrO2. The fact that CeO2 and ZrO2 are in a solid solution can be confirmed by observing whether or not a single-phase diffraction peak derived from the solid solution of CeO2 and ZrO2 is observed using an X-ray diffraction device (XRD). From the viewpoint of increasing the oxide ion conductivity of the solid electrolyte joint of the present invention and further reducing the electrical resistance, the atomic ratio of Zr to Ce in the solid solution, Zr / Ce, is preferably more than 0 and not more than 1.5, more preferably 0.5 to 1.3, and even more preferably 0.8 to 1.2.

[0037] When the oxide containing cerium is (3), the oxide is a solid solution of CeO2 and ZrO2 in which part of Ce is replaced by a rare earth element other than Ce. As the rare earth element other than Ce, from the viewpoint of increasing the oxide ion conductivity of the solid electrolyte joint of the present invention and further reducing the electrical resistance, it is preferable to use Sc, Y, La, Nd, Sm, Eu, Gd, Dy, Ho, Er, Tm, Yb, and Lu, which are rare earth elements other than Ce that form stable trivalent oxides, and it is more preferable to use Sm and Gd. When a rare earth element other than Ce is represented by R, the atomic ratio R / (Ce+Zr) of R to the total of Ce and Zr in the oxide (3) is preferably more than 0 and not more than 0.3, more preferably 0.05 or more and 0.25 or less, and even more preferably 0.1 or more and 0.2 or less, from the viewpoint of increasing the oxide ion conductivity of the solid electrolyte joint of the present invention and further reducing the electrical resistance. In the oxide (3), the atomic ratio of Zr to Ce, Zr / Ce, is preferably more than 0 and not more than 1.5, more preferably 0.5 or more and 1.3 or less, and even more preferably 0.8 or more and 1.2 or less, from the viewpoint of increasing the oxide ion conductivity of the solid electrolyte joint of the present invention and further reducing the electrical resistance, similarly to the oxide (2).

[0038] In the solid electrolyte junction of the present invention, the second electrode is disposed on the surface of the solid electrolyte opposite to the surface facing the first electrode. The second electrode is not particularly limited in the type of material constituting it, as long as it has a function as an electrode for the solid electrolyte, and can be appropriately selected according to the specific application of the solid electrolyte junction. For example, the material contained in the second electrode includes metals such as Ni, Zn, Sn, Li, Au, Ag, Pt, Rh, Pd, alloys and metal oxides containing these elements, carbonates such as lithium carbonate and barium carbonate, mixed conductors containing elements such as La, Sr, Co, and having both oxide ion conductivity and electronic conductivity, and zinc tungstate, and may also be composites of these materials. Alternatively, the material contained in the second electrode may be the same as the material constituting the first electrode. That is, the second electrode may contain platinum or the like and an OSC material.

[0039] The second electrode, like the first electrode described above, preferably has a bicontinuous structure in which the OSC material is bonded by platinum etc. The thickness range of the second electrode can be similar to that of the first electrode.

[0040] Next, a preferred method for producing the solid electrolyte joint of the present invention will be described. The production of a solid electrolyte joint includes a step of forming a first electrode, followed by a step of forming a solid electrolyte and a second electrode. Each step will be described below.

[0041] In the step of forming the first electrode, a substrate is first prepared, and a first electrode is formed on one surface of the substrate. Various thin film forming means are used to form the first electrode. Specifically, the first electrode can be formed by physical vapor deposition (PVD) methods such as vapor deposition, sputtering, and ion plating, or chemical vapor deposition (CVD). Among these various methods, it is preferable to use the sputtering method, since it is easy to form a first electrode having a cocontinuous structure in which the OSC material is bonded by platinum or the like, and it is suitable for mass production.

[0042] When the first electrode is formed by sputtering, a target of platinum or the like and a target of an OSC material are used to form a first electrode containing platinum or the like and an OSC material. In addition, the porosity of the first electrode formed can be controlled by adjusting the gas pressure during sputtering. The porosity of the first electrode can be improved by increasing the gas pressure. The respective ratios of platinum or the like and the OSC material in the first electrode can be adjusted by appropriately setting the power supplied to the target when performing the sputtering method.

[0043] After the first electrode is formed, a solid electrolyte formation step is performed. The solid electrolyte is formed on one of the two surfaces of the first electrode that does not face the substrate. As with the formation of the first electrode, various thin film formation means are used for the formation of the solid electrolyte. Of the thin film formation means, it is preferable to use a sputtering method, since it is easy to form a solid electrolyte having a desired composition.

[0044] After the solid electrolyte is formed, a step of forming a second electrode is performed. The step of forming the second electrode can be performed in the same manner as the step of forming the first electrode. Therefore, it is preferable to form the second electrode by a sputtering method. As a target material for the sputtering method, it is preferable to use a sputtering target material made of platinum or the like and a sputtering target material made of an OSC material.

[0045] Since the first electrode, solid electrolyte, and second electrode formed as described above are all amorphous, it is preferable to crystallize them from the viewpoint of enhancing the OSC ability of the OSC material. From this viewpoint, it is preferable to perform an annealing step after forming the first electrode, the solid electrolyte, or the second electrode, to crystallize the amorphous first electrode, the amorphous solid electrolyte, or the amorphous second electrode. By performing the annealing step, it is possible to reliably generate a cocontinuous structure in which the OSC material is bonded by platinum or the like, i.e., a cermet, in the first electrode and / or the second electrode.

[0046] From the viewpoint of reliable crystallization and reliable formation of the cermet, the annealing temperature is preferably 300°C or higher and 1300°C or lower, more preferably 500°C or higher and 1000°C or lower, and even more preferably 600°C or higher and 900°C or lower. From a similar viewpoint, when an annealing temperature in the above-mentioned range is adopted, the annealing time is preferably from 1 minute to 10 hours, more preferably from 10 minutes to 5 hours, and even more preferably from 30 minutes to 3 hours. The annealing atmosphere is not critical and may be an oxygen-containing atmosphere, a reducing atmosphere, or an inert gas atmosphere.

[0047] The annealing step can be performed once or twice or more times. For example, the first annealing step can be performed after forming the amorphous first electrode and the amorphous solid electrolyte, and then the second annealing step can be performed after forming the amorphous second electrode. Alternatively, the annealing step can be performed only once after forming the amorphous first electrode, the amorphous solid electrolyte, and the amorphous second electrode. Alternatively, the first annealing step can be performed after forming the amorphous first electrode, the second annealing step can be performed after forming the amorphous solid electrolyte, and then the third annealing step can be performed after forming the amorphous second electrode.

[0048] In the above manufacturing method, the first electrode is formed on the substrate, and then the solid electrolyte and the second electrode are formed, but instead of this order, the second electrode may be formed on the substrate first, and then the solid electrolyte and the first electrode are formed. In the latter case, it is preferable to perform an annealing step after the formation of the second electrode, the solid electrolyte, or the first electrode, to crystallize the amorphous second electrode, the amorphous solid electrolyte, or the amorphous first electrode.

[0049] The solid electrolyte junction produced by the above method is suitable for use as a component of an electrochemical device, such as a solid electrolyte fuel cell, a gas sensor such as an oxygen sensor, or a gas permeable device such as an oxygen permeable device.

[0050] 1 to 4 show specific embodiments of the solid electrolyte joint of the present invention. In the solid electrolyte joint 1 of the embodiment shown in FIG. 1, a first electrode 11 is located on a substrate 10, a solid electrolyte 13 is located on the first electrode, and a second electrode 12 is located on the solid electrolyte 13. The substrate 10 is mainly used as a support for the first electrode 11, the solid electrolyte 13, and the second electrode 12. The substrate 10 may be a plate-like body having two opposing main surfaces. There is no particular limitation on the shape of the substrate 10 in a plan view, and it may be any shape, for example, a polygonal shape such as a rectangle, a circle, an ellipse, or the like.

[0051] The thickness of the substrate 10 is preferably 10 μm or more and 1000 μm or less, more preferably 100 μm or more and 650 μm or less, and even more preferably 250 μm or more and 350 μm or less. By setting the thickness of the substrate 10 within this range, the substrate 10 can function sufficiently as a support for the first electrode 11, the solid electrolyte 13, and the second electrode 12. Furthermore, processing into the substrate, such as dicing, can be easily performed. The thickness of the substrate 10 can be measured, for example, by a vernier caliper or a digital thickness measuring device.

[0052] There is no particular limitation on the material constituting the substrate 10, and any material may be used as long as it does not inhibit the electrochemical reaction caused by the solid electrolyte junction 1. Examples of the material include silicon and its compounds, semiconductors such as gallium arsenide, glass such as quartz, metals such as aluminum, copper, nickel, and their alloys, and ceramics such as strontium titanate and magnesia. Among these materials, it is particularly preferable to use silicon in terms of mass productivity and etching properties.

[0053] In the embodiment shown in FIG. 1, a first electrode 11 is disposed on a substrate 10. Alternatively, a second electrode 12 may be disposed on the substrate 10, and a solid electrolyte 13 and a first electrode 11 may be disposed thereon in that order (the same applies to the embodiments shown in FIGS. 2 to 4 described below).

[0054] In the embodiment shown in FIG. 1, a compound containing an element constituting the substrate 10 may be present at the interface between the substrate 10 and the first electrode 11, or a compound containing an element constituting the first electrode in contact with the interface may be present. This compound is generated by the above-mentioned annealing process. For example, when the first electrode 11 is a layer containing an oxide of simple Ce and platinum, etc., a layer consisting of only an oxide of simple Ce is formed on the surface of the substrate 10 facing the first electrode 11. Alternatively, when the substrate 10 is made of silicon, a SiO2 layer is formed on the surface of the substrate 10 facing the first electrode 11.

[0055] In the solid electrolyte joint 1 of the embodiment shown in Fig. 2, at least a part of the upper surface and side surfaces of the first electrode 11 is covered with a solid electrolyte 13. It is sufficient that the upper surface and side surfaces of the first electrode 11 are partly left open and uncovered to be covered with the solid electrolyte 13. The other configurations are the same as those of the embodiment shown in Fig. 1.

[0056] In the solid electrolyte joint 1 of the embodiment shown in Fig. 3, a heater layer 14 is disposed on a substrate 10, a first diffusion rate-controlling layer 15 is disposed on the heater layer 14, and a first electrode 11 is disposed on the first diffusion rate-controlling layer 15. A solid electrolyte 13 and a second electrode 12 are disposed in this order on the first electrode 11. Then, a second diffusion rate-controlling layer 16 is disposed on the second electrode 12. That is, the embodiment shown in Fig. 3 differs from the embodiments shown in Figs. 1 and 2 in that the first electrode 11 is disposed indirectly on the substrate 10 via the heater layer 14 and the first diffusion rate-controlling layer 15.

[0057] In the solid electrolyte joint 1 of this embodiment, as in the embodiment shown in Fig. 2, at least a part of the upper surface and side surface of the first electrode 11 is covered with a solid electrolyte 13. Furthermore, in the solid electrolyte joint 1 of this embodiment, at least a part of the upper surface and side surface of the second electrode 12 is covered with a second diffusion-controlling layer 16. The coverage with the solid electrolyte 13 may be such that a part of the upper surface and side surface of the first electrode 11 or the second electrode 12 is left open and uncovered.

[0058] The heater layer 14 in the solid electrolyte joint 1 of the present embodiment is capable of generating heat. By generating heat from the heater layer 14, the solid electrolyte 13 can be heated, and thus the oxide ion conductivity of the solid electrolyte can be further increased. The heater layer 14 includes a material capable of generating heat. For example, the heater layer 14 may include a metal. By passing a current through the heater layer 14 including a metal, Joule heat is generated, and the heater layer 14 can be heated. Examples of metals include, but are not limited to, platinum, tungsten, and molybdenum. When the heater layer 14 contains a metal, it is preferable that the heater layer 14 contains an electrically insulating material. The electrically insulating material is used for the purpose of electrically insulating the heater layer 14 from the first electrode 11. From this viewpoint, it is preferable to use an oxide as the electrically insulating material. Examples of the oxide include, but are not limited to, tantalum oxide, titanium oxide, silicon oxide, and alumina. By using an oxide as the electrically insulating material, there is an additional advantage that the adhesion between the heater layer 14 and the first electrode 11 is improved.

[0059] The first diffusion rate-limiting layer 15 and the second diffusion rate-limiting layer 16 in the solid electrolyte assembly 1 of this embodiment are used for the purpose of limiting the supply of oxygen gas to the solid electrolyte 13. When the solid electrolyte assembly 1 is used as a current-type oxygen sensor, the current value of the oxygen sensor may fluctuate due to fluctuations in the applied voltage, making it difficult to accurately measure the concentration. In order to prevent this inconvenience, the first diffusion rate-limiting layer 15 and the second diffusion rate-limiting layer 16 are provided to limit the supply of oxygen gas to the solid electrolyte 13 in advance, thereby making it possible to suppress the fluctuation in the current value caused by the above-mentioned fluctuations. For this purpose, the first diffusion rate-limiting layer 15 and the second diffusion rate-limiting layer 16 are preferably made of a porous ceramic material, and in particular, are preferably made of porous alumina. In the embodiment shown in FIG. 3, the solid electrolyte assembly 1 is provided with two diffusion-controlling layers 15 and 16. However, only one of the diffusion-controlling layers may be used, or both of the diffusion-controlling layers may be used, as long as the above-mentioned fluctuation in the current value can be suppressed. For points not specifically explained in the embodiment shown in FIG. 3, the explanations for the embodiment shown in FIGS. 1 and 2 apply as appropriate.

[0060] The embodiment shown in Fig. 4 is a modified example of the embodiment shown in Fig. 3. In the solid electrolyte joint 1 of the embodiment shown in Fig. 4, a hole 17 is formed in the substrate 10. The hole 17 extends in a direction intersecting with the surface of the substrate 10 facing the first electrode 11 (in Fig. 4, a direction perpendicular to the surface). The hole 17 extends so as to penetrate between the two main surfaces of the substrate 10, and is open in each main surface. In other words, the hole 17 is a through hole. The hole 17 is formed for the purpose of improving gas supply, such as supplying oxygen gas to the first electrode 11.

[0061] The hole 17 may be formed over the entire opposing region between the substrate 10 and the first electrode 11, or may be formed in at least a part of the opposing region.

[0062] The shape of the hole 17 opening on the main surface of the substrate 10 may be, for example, a circle. However, the shape of the hole 17 is not limited to this and may be other shapes, for example, a polygon such as a triangle or a rectangle, an ellipse, or a combination of these shapes. In particular, a circle or a regular polygon is preferable.

[0063] A plurality of holes 17 opening on the main surface of the substrate 10 are preferably arranged regularly. There are no particular limitations on the arrangement pattern of the holes 17, and various arrangement patterns can be adopted as long as gas is smoothly supplied to the first electrode 11 through the holes 17. When a plurality of holes 17 are provided, the shortest distance between the outer peripheries of adjacent holes 17 in a plan view of the solid electrolyte assembly 1 is preferably 3 μm to 50 μm on average, more preferably 4 μm to 40 μm, and even more preferably 5 μm to 20 μm, from the viewpoint of increasing the area of ​​the first electrode 11 in contact with the supply gas through the holes 17. By increasing the area of ​​the first electrode 11 in contact with the supply gas, the electrical resistance of the solid electrolyte assembly 1 can be reduced. For example, when the solid electrolyte assembly 1 is used in a solid oxide fuel cell, the output can be improved.

[0064] The hole 17 extends linearly between the two main surfaces of the substrate 10. The hole 17 has the same cross-sectional shape at any position between the two main surfaces of the substrate 10. For example, when the cross-sectional shape of the hole 17 is circular, the hole 17 can be a cylindrical space. Alternatively, as shown in FIG. 4, the cross-sectional shape of the hole 17 can be made different depending on the position between the two main surfaces of the substrate 10. For example, the opening area of ​​the exposed surface of the substrate 10 can be made larger than the opening area of ​​the surface of the substrate 10 facing the heater layer 14. For example, as shown in FIG. 4, the hole 17 can be a space having a truncated cone shape. In this case, the part corresponding to the bottom surface of the truncated cone corresponds to the opening at the exposed surface of the substrate 10, and the part corresponding to the top surface of the truncated cone corresponds to the opening at the surface of the substrate 10 facing the heater layer 14. By forming the hole 17 in this manner, when an electrochemical device including the solid electrolyte joint 1 is used, it is possible to further improve the gas supply, such as the supply of oxygen gas, to the first electrode 11. In this case, when the opening area of ​​the hole 17 on the side facing the heater layer 14 of the substrate 10 is S1 and the opening area of ​​the hole 17 on the exposed surface of the substrate 10 is S2, the value of S2 / S1 is preferably 1 or more and 50 or less, more preferably 2 or more and 25 or less, and even more preferably 5 or more and 15 or less, from the viewpoint of further improving the gas supply to the first electrode 11.

[0065] The opening area of ​​each of the holes 17 on the surface of the substrate 10 facing the heater layer 14 is 300 μm 2 More than 71000μm 2 It is preferable that the thickness is less than 700 μm. 2 More than 8000μm 2 More preferably, it is 1200 μm or less. 2 More than 4000μm 2 It is even more preferable that:

[0066] The hole 17 can be formed by, for example, a dry etching method such as deep etching (DRIE) or a wet etching method such as anisotropic etching. By using these etching methods, the deep hole 17 can be easily formed.

[0067] The dry etching method can be performed using a known photolithography technique. There are no particular limitations on the method of forming a photomask or the type of dry etching gas used when performing the dry etching method, and these may be appropriately selected depending on the material of the substrate 10.

[0068] The wet etching method can also be performed using a known photolithography technique. There are no particular limitations on the method of forming a photomask or the type of chemical solution used when performing the wet etching method, and these may be appropriately selected depending on the material of the substrate 10.

[0069] The shape of the hole 17 formed will be straight when DRIE is used, and will be tapered as shown in FIG. 4 when anisotropic etching is used.

[0070] Although the present invention has been described based on the preferred embodiment, the present invention is not limited to the above embodiment. For example, in the embodiment shown in Figures 1 to 3, the hole 17 formed in the embodiment shown in Figure 4 may be formed in the substrate 10. In the embodiment shown in FIGS. 1 to 4, a substrate which is the same as or different from the substrate 11 may be laminated directly or indirectly on the second electrode 12. EXAMPLES

[0071] The present invention will be described in more detail below with reference to examples, but the scope of the present invention is not limited to these examples.

[0072] Example 1-1 Silicon crystal orientation <100> A substrate with a thickness of 300 μm was prepared. A first electrode with a thickness of 300 nm was formed on one side of this substrate by sputtering. A 2-inch platinum target and a 2-inch oxide containing Ce and Zr (hereinafter referred to as "CZO"; Zr / Ce=1.0) target were used as targets for the sputtering method. Film formation was performed using a co-sputtering method in which power is supplied to the two targets simultaneously. DC sputtering was used for platinum, and RF sputtering was used for CZO. The flow rate of argon gas was 50 sccm, and the argon pressure was 0.5 Pa. The input power was 150 W for platinum and 75 W for CZO, and sputtering was performed at room temperature. The obtained first electrode had a bicontinuous structure in which CZO was bonded by platinum. The first electrode contained 12 volume % CZO and 88 volume % platinum.

[0073] A solid electrolyte was formed on the first electrode by RF sputtering. The solid electrolyte consisted of a 300 nm thick SDC and a 300 nm thick La 9.6 S 5.3 B 0.7 O 26.1 (hereinafter referred to as "LSBO") and a 300 nm thick SDC were sequentially laminated. The flow rate of argon gas in the sputtering method was 50 sccm, and the argon pressure was 0.5 Pa. The input power was 200 W, and sputtering was performed at room temperature.

[0074] The first electrode and solid electrolyte thus formed were annealed in the air at 900° C. for 1 hour. Next, a second electrode with a thickness of 300 nm was formed on the solid electrolyte in the same manner as in the formation of the first electrode. The second electrode contained 12 volume % CZO and 88 volume % platinum. The second electrode thus formed was annealed in an air atmosphere at 900° C. for 1 hour, thereby obtaining the intended solid electrolyte joint.

[0075] [Example 1-2] In Example 1-1, the composition of the first electrode and the second electrode was changed to 41 volume % of CZO and 59 volume % of platinum. A solid electrolyte joint was obtained in the same manner as in Example 1-1 except for this.

[0076] Comparative Example 1-1 In Example 1-1, the composition of the first electrode and the second electrode was changed to 100% by volume of platinum, and otherwise a solid electrolyte joint was obtained in the same manner as in Example 1-1.

[0077] Comparative Example 1-2 In Example 1-1, the composition of the first electrode and the second electrode was 16 volume % of LSBO and 84 volume % of platinum, except for this, a solid electrolyte joint was obtained in the same manner as in Example 1-1.

[0078] Example 2-1 Silicon crystal orientation <100> A substrate with a thickness of 300 μm was prepared. A first electrode with a thickness of 300 nm was formed on one surface of this substrate by sputtering. A 2-inch platinum target and a 4-inch CZO target were used as targets for the sputtering method. Co-sputtering, in which power is supplied to the two targets simultaneously, was used to form the film. DC sputtering was used for platinum, and RF sputtering was used for CZO. The flow rate of argon gas was 50 sccm, and the argon pressure was 4 Pa. The power was 200 W for each, and sputtering was performed at room temperature. The obtained first electrode was porous and had a bicontinuous structure in which CZO was bonded by platinum. The first electrode contained 16 volume % CZO and 84 volume % platinum.

[0079] A solid electrolyte was formed on the first electrode by RF sputtering. The solid electrolyte was formed by sequentially stacking 300 nm thick SDC, 300 nm thick LSBO, and 300 nm thick SDC. The flow rate of argon gas in the sputtering method was 50 sccm, and the argon pressure was 0.5 Pa. The power was 200 W, and sputtering was performed at room temperature.

[0080] Next, a second electrode with a thickness of 300 nm was formed on the solid electrolyte in the same manner as the formation of the first electrode. The second electrode contained 16 volume % CZO and 84 volume % platinum. The first electrode, solid electrolyte, and second electrode thus formed were annealed in air at 900° C. for 1 hour, thereby obtaining the intended solid electrolyte joint.

[0081] Example 2-2 In Example 2-1, the composition of the first electrode and the second electrode was 4 volume % samarium-doped CZO (hereinafter referred to as "Sm-CZO") and 96 volume % platinum. A solid electrolyte joint was obtained in the same manner as in Example 2-1 except for the above. The Sm / (Ce+Zr) atomic ratio in the samarium-doped CZO was 0.12.

[0082] Example 2-3 In Example 2-2, the composition of the first electrode and the second electrode was changed to 18 volume % Sm-CZO and 82 volume % platinum. A solid electrolyte joint was obtained in the same manner as in Example 2-2 except for this.

[0083] Comparative Example 2-1 A solid electrolyte joint was obtained in the same manner as in Example 2-1, except that the composition of the first electrode and the second electrode was changed to 100% by volume of platinum.

[0084] Comparative Example 2-2 In Example 2-1, the composition of the first electrode and the second electrode was changed to 15 volume % of LSBO and 85 volume % of platinum, except for this, a solid electrolyte joint was obtained in the same manner as in Example 2-1.

[0085] [Rating 1] The solid electrolyte junctions obtained in the examples and comparative examples were subjected to electrochemical measurement evaluation at 500°C or 600°C. In detail, the measurement was performed by an AC impedance method using an SI1260 manufactured by Solartron. The measurement conditions were a measurement amplitude of 30 mV and frequencies from 1 kHz to 0.1 kHz. After performing a Nyquist plot using the measurement results, arc fitting was performed using analysis software in the frequency range, and the value of the intersection with the real axis was evaluated as the resistance value. The results are shown in Table 1 below.

[0086] [Evaluation 2] The solid electrolyte assemblies obtained in Example 1-1 and Comparative Example 1-1 were used as oxygen sensors, and their sensor behavior was evaluated by the following method. The ion current value was measured at 600° C. when 0.65 V was applied to the solid electrolyte junctions obtained in Example 1-1 and Comparative Example 1-1. A gas flow of 100% oxygen was performed in a measurement container filled with 21 vol% oxygen + 79 vol% nitrogen. At this time, the ratio of the average ion current value after 550 seconds to 600 seconds to the average ion current value after 300 seconds to 350 seconds when gas replacement was sufficiently performed was compared as the fluctuation rate. The results are shown in Table 1 below.

[0087] [Table 1]

[0088] As is clear from the results shown in Table 1, the solid electrolyte assemblies of the Examples have a lower resistance value than the solid electrolyte assemblies of the Comparative Examples, which is why the sensor behavior is stable. [Explanation of symbols]

[0089] 1 Solid electrolyte assembly 10 Substrate 11 1st electrode 12 2nd electrode 13 Solid electrolyte 14 Heater layer 15 First diffusion-controlling layer 16 Second diffusion-controlling layer 17 Hole

Claims

1. A solid electrolyte junction including a first electrode, a second electrode, and a solid electrolyte located between the first and second electrodes, the solid electrolyte is a ceramic having oxide ion conductivity, the first electrode contains at least one of a platinum group element, gold, and an alloy containing these, and a metal oxide having an oxygen storage capacity; The solid electrolyte joint, wherein the metal oxide comprises at least one oxide selected from the following (2) and (3), and an atomic ratio of Zr to Ce is more than 0 and 1.5 or less: (2) An oxide containing Ce and Zr. (3) An oxide containing Ce and Zr, in which a portion of Ce or Zr is substituted with at least one rare earth element other than Ce.

2. 2. The solid electrolyte joint according to claim 1, wherein the ratio of the metal oxide in the first electrode is 1 vol % or more and 50 vol % or less.

3. 3. The solid electrolyte joint according to claim 1, wherein the first electrode has a thickness of 10 nm or more and 1000 nm or less.

4. 4. The solid electrolyte joint according to claim 1, wherein the metal oxide is (3), and an atomic ratio of rare earth elements other than Ce to a total of Ce and Zr is more than 0 and 0.3 or less.

5. 5. The solid electrolyte joint according to claim 1, wherein the ceramic comprises at least one selected from the group consisting of a composite oxide containing lanthanum and silicon, yttrium-stabilized zirconia, samarium-doped ceria, gadolinium-doped ceria, lanthanum gallate, and yttrium-doped bismuth oxide.

6. 6. The solid electrolyte joint according to claim 1, wherein in the first electrode, at least one of a platinum group element, gold, and an alloy containing these and the metal oxide form a compound or are in a mixed state.

7. The solid electrolyte joint according to claim 1 , further comprising a substrate, the first electrode or the second electrode being disposed on the substrate.

8. 8. The solid electrolyte joint according to claim 1, wherein a compound containing an element constituting the substrate, or a compound containing an element constituting the first electrode or the second electrode in contact with the interface is present at the interface between the substrate and the first electrode or the second electrode.

9. 9. The solid electrolyte joint according to claim 1, wherein the second electrode contains at least one of a platinum group element, gold, and an alloy containing these, and a metal oxide having an oxygen storage capacity.

10. An electrochemical device comprising the solid electrolyte junction according to claim 1 .

11. A method for producing a solid electrolyte junction according to claim 1, comprising the steps of: forming an amorphous first electrode containing at least one of a platinum group element, gold, and an alloy containing these, and a metal oxide having an oxygen storage capacity; forming an amorphous solid electrolyte on the first electrode; forming a second electrode on the solid electrolyte; A method for producing a solid electrolyte junction, comprising: performing a step of forming a first electrode, followed by a step of forming a solid electrolyte and a step of forming a second electrode; or performing a step of forming a second electrode, followed by a step of forming a solid electrolyte and a step of forming a first electrode.

12. 12. The method for producing a solid electrolyte joint according to claim 11, wherein either the first electrode or the second electrode is formed on a substrate by a sputtering method.

13. 13. The method for producing a solid electrolyte joint according to claim 11, wherein when at least one of the first electrode and the second electrode is formed, a sputtering target material made of a platinum group element, gold, or an alloy containing these, and a sputtering target material made of a metal oxide having an oxygen storage capacity are used.

14. 14. The method for producing a solid electrolyte joint according to claim 11, further comprising: performing an annealing step after forming the first electrode, after forming the solid electrolyte, or after forming the second electrode, to crystallize the amorphous first electrode, the solid electrolyte, or the second electrode.

Citation Information

Patent Citations

  • Mixed conductive multiple oxide for oxygen separation and manufacturing method therefor

    JP2003206178A

  • Electrochemical device

    JP2008251379A

  • Gold catalysts on ceria-containing supports

    JP2008540126A

  • Noble metal nanostructure and electrochemical reactor

    JP2009090448A

  • Electrode catalyst of oxygen electrode for solid oxide type steam electrolytic cell, and production method of the same

    JP2014034727A